11. Kerja Sama Economic Community Of West African States (Ecowas) dalam Menanggulangi Perompakan Maritim di Teluk Guinea Tahun 2008 - 2015 - Ardi, Vito Yanufan; Windiani, Reni; Pattipelohy, Shary Charlotte (Journal of International Relations, 2017)
Geo-economy in Gulf of Guinea threatened by high number of maritime piracy in region.ECOWAS as a regional actor in Gulf of Guinea has responsible to keep its maritime areasecure. For combating maritime piracy in Gulf of Guinea, ECOWAS has cooperatedinternally among the members even with other regional actor (ECCAS) and internationalactors. This research aims to analyze the effectiveness of of ECOWAS, regional andGlobal cooperations in combating maritime piracy. This research uses Regional SecurityComplex theory and States, Powers and Security theory for analyzing the high number ofmaritime piracy in Gulf of Guinea. This research also uses qualitative method withdescriptive-explanative through interview and literature research. However, based frompiracy attacks which has not been decreasing yet, huge financial loss from combatingpiracy, even victims numbers which still on high level, indicating that ECOWAScooperations for combating piracy in region is not effective yet. Analysis States, Powersand Security suggest ECOWAS as weak states. The weakness of ECOWAS membersstates in economic, politic and social sectors make maritime piracy flourishing in Gulf of